Treatment of patients with recurrent epithelial ovarian cancer for whom platinum is still an option. (18th March 2019) - Buechel, M; Herzog, T J; Westin, S N; Coleman, R L; Monk, B J; Moore, K N
Abstract: Background: Ovarian cancer remains the most deadly gynecologic cancer with the majority of patients relapsing within 3 years of diagnosis. Traditional treatment paradigms linked to platinum sensitivity or resistance are currently being questioned in the setting of new diagnostic methods and treatment options. Design: Authors carried out review of the literature on key topics in treatment of recurrent epithelial ovarian cancer (EOC) when platinum is still an option; including secondary surgical cytoreduction, chemotherapy, novel treatment options, and maintenance therapy. A treatment algorithm is proposed. Results: Molecular characterization of EOC is critical to help guide treatment decisions. The role of secondary cytoreductive surgery is currently being evaluated with results from Gynecologic Oncology Group (GOG) 213 and anticipated results from DESKTOP III clinical trials. Chemotherapy backbone has remained relatively unchanged but utilizing non-platinum-based regimens is under investigation. In addition, maintenance therapy with anti-angiogenic therapy and Poly (ADP-ribose) Polymerase (PARP) inhibitors has emerged as the standard of care. Novel combinations, including immunotherapy and anti-angiogenesis agents, may further change the current landscape. Conclusions: The treatment of recurrent EOC is rapidly changing. Clinical trial design will need to continue to evolve as many novel therapies move to the upfront setting. Ultimately, the treatment of patients with recurrent EOC must incorporate individual patient and tumor factors.